Provider Factors and Patient-Reported Healthcare Discrimination in the Diabetes Study of California (DISTANCE) - Lyles, Courtney R. (2011)
OBJECTIVE: We examined provider-level factors and reported discrimination in the healthcare setting. METHODS: With data from the Diabetes Study of Northern California (DISTANCE)—a race-stratified survey of diabetes patients in Kaiser Permanente Northern California—we analyzed patient-reported racial/ethnic discrimination from providers. Primary exposures were characteristics of the primary care provider (PCP, who coordinates care in this system), including specialty/type, and patient-provider relationship variables including racial concordance. RESULTS: Subjects (n=12,151) included 20% black, 20% Latino, 23% Asian, 30% white, and 6% other patients, with 2% to 8% reporting discrimination by racial/ethnic group. Patients seeing nurse practitioners as their PCP (OR=0.09; 95% CI: 0.01–0.67), those rating their provider higher on communication (OR=0.70; 95% CI: 0.66–0.74) were less likely to report discrimination, while those with more visits (OR=1.10; 95% CI: 1.03–1.18) were more likely to report discrimination. Racial concordance was not significant once adjusting for patient race/ethnicity. CONCLUSIONS: Among diverse diabetes patients in managed care, provider type and communication were significantly related to patient-reported discrimination. PRACTICE IMPLICATIONS: Given potential negative impacts on patient satisfaction and treatment decisions, future studies should investigate which interpersonal aspects of the provider-patient relationship reduce patient perceptions of unfair treatment.